2020
DOI: 10.1038/s41746-020-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual-patient prediction of meningioma malignancy and survival using the Surveillance, Epidemiology, and End Results database

Abstract: Meningiomas are known to have relatively lower aggressiveness and better outcomes than other central nervous system (CNS) tumors. However, there is considerable overlap between clinical and radiological features characterizing benign, atypical, and malignant tumors. In this study, we developed methods and a practical app designed to assist with the diagnosis and prognosis of meningiomas. Statistical learning models were trained and validated on 62,844 patients from the Surveillance, Epidemiology, and End Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
(59 reference statements)
1
21
0
1
Order By: Relevance
“…The purpose of such models include: informing patients of the risk of onset or prognosis, screening high-risk groups, and helping doctors make clinical decisions. In 2003, van Zee et al [14] rst proposed a nomogram model to predict the risk of non-sentinel lymph node metastasis in sentinel node-positive breast cancer. This nomogram was based on a regression model to intuitively present the probability of outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of such models include: informing patients of the risk of onset or prognosis, screening high-risk groups, and helping doctors make clinical decisions. In 2003, van Zee et al [14] rst proposed a nomogram model to predict the risk of non-sentinel lymph node metastasis in sentinel node-positive breast cancer. This nomogram was based on a regression model to intuitively present the probability of outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In absolute numbers, those known as benign meningiomas (grade I) are much more common than borderline malignant or malignant meningiomas (grade II-III). 15,16 The current global prevalence for meningiomas is estimated three times higher for females. Also is reported an incidence peak between 30 and 59 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The Central Brain Tumor Registry of the United States (CBTRUS) reported an incidence of 6.0 per 100,000 inhabitants . 1 Meanwhile Moreau et al 2 , reported in 2020 an incidence of 8.14 per 100,000 inhabitants. The estimated prevalence ranges between 1 and 2,7%, and about 85% are diagnosed as screening.…”
Section: Introductionmentioning
confidence: 97%
“…1 Open access AI systems often -even to the ignorance of their creators -replicate the societal biases extant within the data they are trained on. In our own study, 10 we found that the models we had trained on data from over 60 000 patients from a national cancer registry to predict meningioma malignancy and survival predicted worse survival for black and uninsured patients. Another study which developed an algorithm to predict no-show appointments in paediatric orthopaedic clinics likewise identified that insurance type was a significant factor in predicting the rate of no-shows.…”
Section: Companies (>Us$1b)mentioning
confidence: 99%